The complete list of Ramsey (2K_2,K_4)-minimal graphs - Kristiana Wijaya; Edy Tri Baskoro; Hilda Assiyatun; Djoko Suprijanto (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2015)
Let F, G, and H be non-empty graphs. The notation F → (G,H) means that if all edges of F are arbitrarily colored by red or blue, then either the subgraph of F induced by all red edges contains a graph G or the subgraph of F induced by all blue edges contains a graph H. A graph F satisfying two conditions: F → (G,H) and (F-e) rightarrow (G,H) for every e E(F) is called a Ramsey (G,H)-minimal graph. In this paper, we determine all non-isomorphic Ramsey (2K_2,K_4)-minimal graphs.